Method for preparing pravastatin-loading vascular tissue engineering scaffold material by electrospinning - ZHAO PENG; CAI KAICAN; LU LING; CHEN ZHIRU; LI XINGPING; HU XIANG (2018)
The invention relates to a method for preparing a pravastatin-loading vascular tissue engineering scaffold material by electrospinning. The method comprises: (1) preparing a polyhydroxyalkanoate solution; (2) preparing a pravastatin sodium solution; 3) preparing an electrospinning solution; and (4) electrospinning to obtain a vascular tissue engineering scaffold material. According to the presentinvention, the hydrophilic pravastatin sodium is loaded into the hydrophobic polyhydroxyalkanoate matrix, such that the prepared vascular tissue engineering scaffold material can achieve the long-acting release of pravastatin. 本发明涉及静电纺丝法制备载有普伐他汀血管组织工程支架材料的方法，该方法由以下步骤组成(1)配制聚羟基烷酸酯溶液；(2)配制普伐他汀钠溶液；(3)制备静电纺丝液；(4)静电纺丝制得血管组织工程支架材料。本发明将亲水性的普伐他汀钠载入到疏水性的聚羟基烷酸酯基质中，所制备的血管组织工程支架材料，可长效释放普伐他汀。